Using of Seating Arrangement and Teachers' Role in English Language Teaching to Increase Student Speaking Ability - Anita Susanti (IAI Ma'arif NUMetro Lampung, 2017)
Most of schools or universities use conventional or traditional seating arrangement in teaching and learning process. Sometimes, students' chairs have little wooden palettes on one of the arms to provide a surface to write on. Sometimes, the students have desks in front of them. It has many problems to teach speaking when use these seating arrangement. These problems make some teachers or lecturers arrange the proper seating arrangement. Beside that, teacher role to manage it and conduct learning and teaching activities also have crucial part to increase students' speaking ability. How teacher talk and behave can influence students' ability to master the material has given. The main focus of this research is using of seating arrangement and teachers' role in English language teaching to increase students' speaking ability at STKIP Kumala Lampung Metro. Data came from students involving writer and an english lecturer. The research was conducted through a Classroom Action Research (CAR). The result showed that seating arrangement and teachers' role in teaching could be used to increase students' speaking in learning English.  The successful using of seating arrangement and teachers' role can be seen from the students' positive response and their active participation in speaking learning activities.   Keyword : Speaking, Seating arrangement, Teachers' role, English.